2017
DOI: 10.1111/epi.13980
|View full text |Cite
|
Sign up to set email alerts
|

ADGRV1 is implicated in myoclonic epilepsy

Abstract: Our data suggest that the ADGRV1 variation contributes to epilepsy with myoclonic seizures, although the inheritance pattern may be complex in many cases. In patients with 5q14.3 deletion and epilepsy, ADGRV1 haploinsufficiency likely contributes to seizure development. The latter is a shift from current thinking, as MEF2C haploinsufficiency has been considered the main cause of epilepsy in 5q14.3 deletion syndrome. In cases of 5q14.3 deletion and epilepsy, seizures likely occur due to haploinsufficiency of on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 44 publications
(85 reference statements)
2
30
1
Order By: Relevance
“…Knockout mice without exons 2–4 of Avlgr1b were prone to experience audiogenic reflex seizure, although obvious cerebral histological abnormalities were not proven [ 29 ]. Differing from previous patients with ultra-rare ADGRV1 variants [ 26 , 30 ], our patient showed febrile seizures with afebrile seizures.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Knockout mice without exons 2–4 of Avlgr1b were prone to experience audiogenic reflex seizure, although obvious cerebral histological abnormalities were not proven [ 29 ]. Differing from previous patients with ultra-rare ADGRV1 variants [ 26 , 30 ], our patient showed febrile seizures with afebrile seizures.…”
Section: Discussioncontrasting
confidence: 76%
“…On the other hand, ADGRV 1 variation plays a part in developing epilepsy with myoclonic seizures, although the inheritance manner may be different in various patients [ 30 ]. The function of ADGRV1 is unestablished, but multiple calcium exchanger b-repeats in the ectodomain imply a contribution to protein–protein interaction that may be calcium mediated [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…While this needs to be functionally validated, it may widen our concept of the genetic spectrum of epilepsy in adulthood, which may in turn guide the development of adequate treatment options. ADGRV1 haploinsufficiency may be an important contributor to the development of genetic epilepsies, particularly those with myoclonic seizures (Myers et al, 2018). In our study, three APEs with the ADGRV1 heterozygous variant (p.His1859Arg) had either focal or generalized epilepsy, which might be plausible if a focal myoclonic seizure was confused with a focal motor seizure, as is occasionally the case in outpatient clinics.…”
Section: Genotype-phenotype Correlationsupporting
confidence: 50%
“…Furthermore, several severe patients carried variants in genes that were previously described to worsen phenotypes (POLG , SCN2A , CACNA1A , and CACNA1G), strengthening those associations (Calhoun et al, ; Gaily et al, ; Hawkins et al, ; Ohmori et al, ). GPR98 , a gene implicated in myoclonic epilepsy (Myers et al, ), showed the highest overrepresentation of variants in severe patients in three categories of variants, and SCN10A , another sodium channel alpha‐subunit gene, was most often implicated in mild patients. One relatively severe patient carried a GABRA3 variant (family 6); several GABA receptor genes have already been suggested as potential SCN1A modifiers (Miller et al, ).…”
Section: Discussionmentioning
confidence: 99%